2016
DOI: 10.1021/acs.nanolett.5b04499
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Mean Free Path Spectra of Thermal Phonons Along the c-Axis of Graphite

Abstract: Heat conduction in graphite has been studied for decades because of its exceptionally large thermal anisotropy. While the bulk thermal conductivities along the in-plane and cross-plane

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
75
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 50 publications
16
75
2
Order By: Relevance
“…Encased 10-layer graphene has a thermal conductivity larger than 1000 W/(m K) (Jang, et al, 2013), and the supported graphene of 34 layers is found to fully recover to the bulk value of graphite (Sadeghi, et al, 2013). The large thickness required to ensure a higher thermal conductivity of encased and supported graphene is probably due to the long mean free paths of phonons in graphite along the crossplane direction, which was revealed recently by MD simulations (Wei, et al, 2014b) and confirmed by experimental measurements (Fu, et al, 2015;Zhang, et al, 2016).…”
Section: E1 Thermal Conductivity Of Supported 2-d Materialsmentioning
confidence: 59%
“…Encased 10-layer graphene has a thermal conductivity larger than 1000 W/(m K) (Jang, et al, 2013), and the supported graphene of 34 layers is found to fully recover to the bulk value of graphite (Sadeghi, et al, 2013). The large thickness required to ensure a higher thermal conductivity of encased and supported graphene is probably due to the long mean free paths of phonons in graphite along the crossplane direction, which was revealed recently by MD simulations (Wei, et al, 2014b) and confirmed by experimental measurements (Fu, et al, 2015;Zhang, et al, 2016).…”
Section: E1 Thermal Conductivity Of Supported 2-d Materialsmentioning
confidence: 59%
“…Since the induced temperature oscillation depends on the thermal properties of the samples, TDTR is an accurate approach to measure the thermal conductivity of nanostructures. [49][50][51] In this study, we used a 1/e 2 laser radius of 10 lm, a modulation frequency of 10 MHz, and a total laser power of $40 mW to limit the steady state temperature rise to <10 K. The thermal conductivities of Cr 1-x Sc x N were then derived by comparing the TDTR measurements to the calculations of a thermal model. 52 In the analysis, we used the thickness of Al film derived from picosecond acoustics, 53 the heat capacity of CrN and ScN from their bulk values, 54,55 and the heat capacity of Cr 1-x Sc x N alloy films estimated from virtual crystal approximation.…”
Section: E Thermoelectric Properties Measurementsmentioning
confidence: 99%
“…Phonon MFPs of typical crystalline semiconductors such as Si, GaN, and graphite are on the order of tens of nanometers to micrometers. [10][11][12] Accordingly, evident phonon interference effects were observed by both experimental work and theoretical analysis on phonon transport across superlattices, i.e., alternative nanoscopic layers of epitaxially bonded semiconductors such as GaAs and AlAs. 2,[13][14][15] For amorphous materials such as amorphous silica (aSiO 2 ), however, the traveling phonons can be diffusely scattered by the disordered structure, which significantly limits the phonon MFP.…”
Section: Introductionmentioning
confidence: 99%